Determining the longitudinal accuracy and reproducibility of T1 and T2 in a 3T MRI scanner. Issue 11 (25th September 2021) - Carr, Madeline E.; Keenan, Kathryn E.; Rai, Robba; Metcalfe, Peter; Walker, Amy; Holloway, Lois
Abstract: Purpose: To determine baseline accuracy and reproducibility of T1 and T2 relaxation times over 12 months on a dedicated radiotherapy MRI scanner. Methods: An International Society of Magnetic Resonance in Medicine/National Institute of Standards and Technology (ISMRM/NIST) System Phantom was scanned monthly on a 3T MRI scanner for 1 year. T1 was measured using inversion recovery (T1 ‐IR) and variable flip angle (T1 ‐VFA) sequences and T2 was measured using a multi‐echo spin echo (T2 ‐SE) sequence. For each vial in the phantom, accuracy errors (%bias) were determined by the relative differences in measured T1 and T2 times compared to reference values. Reproducibility was measured by the coefficient of variation (CV) of T1 and T2 measurements across monthly scans. Accuracy and reproducibility were mainly assessed on vials with relaxation times expected to be in physiological ranges at 3T. Results: A strong linear correlation between measured and reference relaxation times was found for all sequences tested ( R 2  > 0.997). Baseline bias (and CV[%]) for T1 ‐IR, T1 ‐VFA and T2 ‐SE sequences were +2.0% (2.1), +6.5% (4.2), and +8.5% (1.9), respectively. Conclusions: The accuracy and reproducibility of T1 and T2 on the scanner were considered sufficient for the sequences tested. No longitudinal trends of variation were deduced, suggesting less frequent measurements are required following the establishment of baselines.